Disseminated tetracycline resistance in oral streptococci: implication of a conjugative transposon. - Hartley, D L (1984)
A DNA sequence specifying tetracycline resistance (Tcr) has been previously cloned from a clinical isolate of Streptococcus mutans designated U202 (J. A. Tobian and F. L. Macrina, J. Bacteriol. 152:215-222, 1982). We used this sequence as a molecular probe in studying the dissemination of Tcr among oral streptococcal species isolated from patients treated with tetracycline. Eleven strains (including S. sanguis I, S. sanguis II, S. mitis, and S. salivarius) from seven patients were examined by Southern blot analysis. Seven strains showed strong hybridization to the Tcr probe, two showed weak hybridization, and two did not display detectable hybridization. Based on previous characterization of the cloned sequence, our data suggest the dissemination of the tetM class of resistance determinants among these oral streptococci. One of the clinical S. sanguis I isolates studied was able to transfer its Tcr phenotype to other oral streptococci and to enteric streptococci in the absence of plasmid DNA. This transfer appeared to be conjugation-like on the basis of its insensitivity to DNase and its dependence on intimate cell-to-cell contact. Using the cloned Tcr sequence, we were able to study the progeny of the matings. Our data suggest that this resistance transfer element occupies a chromosomal location in streptococcal cells and that it strongly resembles the conjugative transposon Tn916 in its behavior.